2017
DOI: 10.1038/s41598-017-16869-2
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferons drive inflammasome-independent emergency monocytopoiesis during endotoxemia

Abstract: Emergency monocytopoiesis is an inflammation-driven hematological process that supplies the periphery with monocytes and subsequently with macrophages and monocyte-derived dendritic cells. Yet, the regulatory mechanisms by which early bone marrow myeloid progenitors commit to monocyte-derived phagocytes during endotoxemia remains elusive. Herein, we show that type I interferons signaling promotes the differentiation of monocyte-derived phagocytes at the level of their progenitors during a mouse model of endoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 76 publications
2
16
1
Order By: Relevance
“…Next, we assessed the role of other pro-inflammatory cytokines including type I IFNs, TNF-α, and IL-6, all of which are known to trigger emergency myelopoiesis, in altered DC differentiation [ 34 , 37 , 39 , 44 46 ]. The abrogation of type I IFN signalling did not influence the numbers of CDPs and pre-DCs in the BM ( Fig 6D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we assessed the role of other pro-inflammatory cytokines including type I IFNs, TNF-α, and IL-6, all of which are known to trigger emergency myelopoiesis, in altered DC differentiation [ 34 , 37 , 39 , 44 46 ]. The abrogation of type I IFN signalling did not influence the numbers of CDPs and pre-DCs in the BM ( Fig 6D ).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that the pro-inflammatory cytokine storm following IAV infection is responsible for altering DC development in the BM. It has been reported that type I IFNs, IL-6 and TNF-α promote emergency monopoiesis in some settings [ 39 , 60 , 61 ]. Here, we found that the decrease in the number of CDPs and pre-DCs during IAV infection is independent of these cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipopolysaccharides (LPS) of the Gram negative bacilli Yersinia enterocolitica are sensed by radio-resistant cells that produce IFNγ, inducing a selective differentiation of myeloid progenitors toward the monocytic lineage (monocytopoiesis) at the expense of conventional DC (cDC) ( 17 ). Moreover, R848 and LPS induce the production of type I IFN involved in the differentiation of myeloid progenitors toward the monocytic lineage ( 18 , 19 ). cDC, conventional dendritic cell; CDP, common dendritic cell progenitor; Pre-DC, precursor of cDCs; pDC, plasmacytoide DC; cMoP, common monocyte progenitor; Mo-DC, monocyte-derived dendritic cells, Mo-Mac, monocyte-derived macrophages; IFNγ, interferon γ; TLR toll-like receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these cytokines are induced by these danger signals, such as type I IFN. Indeed, type I IFN gives rise to Mo-APCs by acting through the IFNAR receptor on direct monocyte progenitors (Figure 1 ) ( 18 ). Similar to DAMPs, microbiota-dependent metabolites affect the balance between Mo-DCs and macrophages.…”
Section: Introductionmentioning
confidence: 99%